Development and Validation of a RP-HPLC Method for Simultaneous Determination of Levofloxacin and Moxifloxacin in Pharmaceutical Dosage Forms - Farjahan Nur,; Asma Rahman,; Md. Zakir Sultan,; Md. Gias Uddin,; Mohammad A. Rashid,; Amir Hassan ,; Mansoor Ahmed, (Journal of Basic & Applied Sciences, 2021)
A simple, fast and economic reversed phase high performance liquid chromatographic (HPLC) method has been successfully developed and validated for simultaneous determination of fluoroquinolone analogs namely levofloxacin and moxifloxacin in both pure form (as API) and in pharmaceutical dosage forms. The method was validated according to the guidelines of ICH, FDA and USP with respect to accuracy, precision and linearity. For method development a C-18 bonded silica column (250 x 4.6 mm, 5μ, Phenomenex, Inc) was used with a mobile phase comprising of 10% aqueous solution of acetic acid and acetonitrile in a ratio of 80:20 v/v. The flow rate was 0.5 mL/min and effluents were monitored at 300 nm and the retention times were found to be at 7.0±0.1 min and 10.59±0.1 min for levofloxacin and moxifloxacin, respectively. The recovery was found to be more than 99% for each spiked samples of levofloxacin and moxifloxacin, demonstrating the accuracy of the protocol. Intra-day and inter-day precisions of the new method were less than the maximum allowable limit (RSD% £ 2.0) according to FDA. The method showed linear response with correlation coefficient value of 0.9975 in both the cases. Therefore, the developed method was found to be simpler, accurate, reproducible, efficient and less time consuming and can be successfully applied for the simultaneous assay of levofloxacin and moxifloxacin formulations.HPLC, method development, validation, levofloxacin, moxifloxacin.